Potent efficacy of combined PI3K/mTOR and JAK or ABL inhibition in murine xenograft models of Ph-like acute lymphoblastic leukemia - Tasian, Sarah K.; Teachey, David T.; Li, Yong; Shen, Feng; Harvey, Richard C.; Chen, I-Ming; Ryan, Theresa; Vincent, Tiffaney L.; Willman, Cheryl L.; Perl, Alexander E.; Hunger, Stephen P.; Loh, Mignon L.; et al. (Blood, 2017)
Philadelphia chromosome (Ph)–like B-cell acute lymphoblastic leukemia (Ph-like ALL) is associated with activated JAK/STAT, Abelson kinase (ABL), and/or phosphatidylinositol 3-kinase (PI3K) signaling and poor clinical outcomes. PI3K pathway signaling inhibitors have been minimally investigated in Ph-like ALL. We hypothesized that targeted inhibition of PI3Kα, PI3Kδ, PI3K/mTOR, or target of rapamycin complex 1/2 (TORC1/TORC2) would decrease leukemia proliferation and abrogate aberrant kinase signaling and that combined PI3K pathway and JAK inhibition or PI3K pathway and SRC/ABL inhibition would have superior efficacy compared to inhibitor monotherapy. We treated 10 childhood ALL patient-derived xenograft models harboring various Ph-like genomic alterations with 4 discrete PI3K pathway protein inhibitors and observed marked leukemia reduction and in vivo signaling inhibition in all models. Treatment with dual PI3K/mTOR inhibitor gedatolisib resulted in near eradication of ALL in cytokine receptor-like factor 2 (CRLF2)/JAK-mutant models with mean 92.2% (range, 86.0%-99.4%) reduction vs vehicle controls (P < .0001) and in prolonged animal survival. Gedatolisib also inhibited ALL proliferation in ABL/platelet-derived growth factor receptor (PDGFR)-mutant models with mean 66.9% (range, 42.0%-87.6%) reduction vs vehicle (P < .0001). Combined gedatolisib and ruxolitinib treatment of CRLF2/JAK-mutant models more effectively inhibited ALL proliferation than either inhibitor alone (P < .001) and further enhanced survival. Similarly, superior efficacy of combined gedatolisib and dasatinib was observed in ABL/PDGFR-mutant models (P < .001). Overall, PI3K/mTOR inhibition potently decreased ALL burden in vivo; antileukemia activity was further enhanced with combination inhibitor therapy. Clinical trials testing combinations of kinase inhibitors in Ph-like ALL patients are indicated. •PI3K/mTOR inhibition potently inhibited leukemia proliferation and signal transduction in vivo in human Ph-like ALL xenograft models.•Combined PI3K/mTOR and JAK or ABL inhibition was superior to monotherapy in CRLF2/JAK-mutant and ABL/PDGFR-mutant Ph-like ALL models.